The Influence of Upwelling on Key Bivalves from the Humboldt and Iberian Current Systems - Garcia-Herrera, C (Elsevier Ltd, 2023)
Eastern Boundary Upwelling Systems (EBUS) deliver cold, nutrient-rich waters, influencing coastal biota from the molecular to the ecosystem level. Although local upwelling (U) and downwelling (DU) conditions are often known, their influence on body attributes of relevant species has not been systematically compared within and between EBUS (i.e., below and above regional scales). Hence, we compared the physical-chemical characteristics of U and DU sites in the Humboldt Current system (Chile) and the Iberian Current system (Portugal). We then assessed the influence of U and DU upon eight body attributes in purple mussels (Perumytilus purpuratus) and Mediterranean mussels (Mytilus galloprovincialis), from the Humboldt and Iberian systems, respectively. We hypothesized that bivalves from U sites display better fitness, as measured by body attributes, regardless of their origin (EBUS). As expected, waters from U sites in both systems showed lower temperatures and pH, and higher nitrite concentrations. We also found that mussels from U sites showed better fitness than those in DU sites in 12 out of 16 direct U vs DU comparisons. Shell length, shell volume, organic content of soft-tissues, and mechanical properties of the shell averaged consistently higher in mussels from U sites in both Current systems. In addition, total weight, soft-tissue weight, shell weight and shell thickness were all higher in the U site at the Humboldt system but had less consistent differences at the Iberian system. Altogether, most results supported our working hypothesis and indicate that U conditions support better fitted mussels. The few attributes that did not exhibit the expected U vs DU differences in the Iberian system suggest that local and species-specific differences also play a role on the attributes of these species. These results may also serve as a reference point for further studies addressing the influence of upwelling in these productive, critically important systems. © 2023 Elsevier Ltd